Vitreomacular interface alterations following peripheral laser retinopexy: Interface changes after laser. Issue 5 (September 2020) - Tosi, Gian Marco; Bacci, Tommaso; Tarantello, Antonio; Marigliani, Davide; Calmanti, Giacomo; Polito, Maria Sole; Neri, Giovanni; Fusco, Fiorella; Cevenini, Gabriele; Virgili, Gianni
Aim: To demonstrate the morphological outcomes of macular hole following prophylactic peripheral laser retinopexy (PPLR). Methods: Our retrospective case-control analysis included 92 eyes, 55 in the laser group and 37 in the non-laser group. Fifty-five patients were subjected to prophylactic peripheral laser retinopexy in preparation for pars plana vitrectomy for macular hole, with and without vitreomacular adhesion (laser group). Before and after prophylactic peripheral laser retinopexy, we evaluated any changes in vitreomacular anatomy by optical coherence tomography. Optical coherence tomography changes were also analyzed in the visits preceding pars plana vitrectomy in 37 macular hole eyes not subjected to prophylactic peripheral laser retinopexy (non-laser group). Results: In the laser group, 7 out of 55 eyes (12.7%) showed macular hole closure (6 out of 18 macular hole eyes with vitreomacular adhesion (33.3%) and 1 out of 37 eyes without vitreomacular adhesion (2.7%)), while no patients showed macular hole closure in the non-laser group (p < 0.05). The mean width of the seven closed macular hole was 191.4 µm (range: 59–282 µm). In all except one of the six macular hole eyes with vitreomacular adhesion, the macular hole closed without vitreomacular adhesion release. In our analysis of the patient subgroup with vitreomacular adhesion, we observed a release of vitreomacular adhesion in 3 out of 18 eyes (16.6%) in the laser group and in 1 out of 13 eyes (7.6%) in the non-laser group (p > 0.05). Conclusion: These findings support a possible beneficial role for prophylactic peripheral laser retinopexy in selected individuals with macular hole.